An updated checklist of Azorean arthropods (Arthropoda) - Borges, Paulo A. V. (2022)
BACKGROUND: The Azores is a remote oceanic archipelago of nine islands which belongs to the Macaronesia biogeographical region hosting a unique biodiversity. The present Azorean landscape is strongly modified by the presence of man and only in small areas, where the soil or climate was too rough, have primitive conditions remained unchanged. Despite the fact that most of the Azorean native habitats are now lost, a large number of endemic species are still present and need urgent conservation. The present checklist of terrestrial and freshwater arthropods of the Azores Archipelago is based on all known published literature. The main goal of this work is to list, as rigorously as possible, all the known terrestrial and freshwater arthropods of the Azores. In this way, we are contributing to solve the ‘Linnaean’ shortfall, i.e. an incomplete taxonomic description of species-level diversity and the Wallacean Biodiversity Shortfall, the incomplete species distribution knowledge. NEW INFORMATION: The checklist includes new records of arthropods at island and archipelago levels that were published in the last twelve years. Compared to the last checklist of Azorean arthropods (Borges et al. 2010b), a total of 217 taxa (species and subspecies) are added. Currently, the total number of terrestrial and freshwater arthropod species and subspecies in the Azores is estimated to be 2420 taxa belonging to 14 classes, 53 orders, 440 families, 1556 genera, 2400 species and 149 individual subspecies. The most diverse orders of Azorean arthropods are: Coleoptera (585 taxa), Diptera (423 taxa), Hemiptera (338 taxa), Hymenoptera (163 taxa), Lepidoptera (159 taxa) and Araneae (133 taxa). A total of 276 endemic taxa are currently known (232 species and 44 subspecies), belonging to eight classes and 22 orders. São Miguel, Terceira and Pico are the islands with higher number of endemic species and subspecies. In the Azores, the number of native non-endemic taxa is 793 taxa, totalling 1069 indigenous taxa. Compared to the other nearest Macaronesian archipelagos (Madeira and Canaries), the Azorean arthropod fauna is characterised by a lower percentage of endemism (endemics/indigenous: 26% in Azores, 47% in Madeira Archipelago and 42% in Canary Islands) and a high proportion of exotic introduced taxa (39% in Azores, 19% in Madeira Archipelago and 8% in Canary Islands). Based on recent IUCN Red-listing of Azorean arthropods, a large fraction of the endemic taxa is under high threat.